The effect of force on thermodynamics and kinetics: unfolding single RNA molecules. (26th October 2004) - Tinoco, I.; Collin, D.; Li, P.T.X.
Abstract : We have used laser tweezers to unfold single RNA molecules at room temperature and in physiological-type solvents. The forces necessary to unfold the RNAs are over the range 10–20 pN, forces that can be generated by cellular enzymes. The Gibbs free energy for the unfolding of TAR (transactivation-responsive) RNA from HIV was found to be increased after the addition of argininamide; the TAR hairpin was stabilized. The rate of unfolding was decreased and the rate of folding was increased by argininamide.